2006
DOI: 10.1016/j.pain.2005.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy improves severe pain associated with fibromyalgia

Abstract: The pathophysiology of fibromyalgia remains unknown. Several reports have recently suggested the novel concept that fibromyalgia is due to the central nervous system becoming hyper-responsive to a peripheral stimulus. The effect of electroconvulsive therapy (ECT) as pain remedication in cases of fibromyalgia without major depressive disorder was studied in a prospective trial lasting three months. All of the patients taking part in the study fulfilled the American College of Rheumatology diagnostic criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
0
25
0
1
Order By: Relevance
“…Their hypersensitivity is, however, generalized and not confined to a specific neuroanatomically defined body part (Gormsen, Bach, Rosenberg & Jensen, ). The etiology of FM is still medically unexplained (Arnold, Lu, Crofford et al ., ; Arnold, Rosen, Pritchett ; Bennett, ; McLean & Clauw, ; Usui, Doi, Nishioka et al ., ). It is, however, hypothesized that there is a dysfunction in the descending inhibitory pathways mediated by serotonin and noradrenaline in the spinal cord and brain (Gormsen, et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Their hypersensitivity is, however, generalized and not confined to a specific neuroanatomically defined body part (Gormsen, Bach, Rosenberg & Jensen, ). The etiology of FM is still medically unexplained (Arnold, Lu, Crofford et al ., ; Arnold, Rosen, Pritchett ; Bennett, ; McLean & Clauw, ; Usui, Doi, Nishioka et al ., ). It is, however, hypothesized that there is a dysfunction in the descending inhibitory pathways mediated by serotonin and noradrenaline in the spinal cord and brain (Gormsen, et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In reality, trait anxiety is an individual factor that tends to lead to chronic pain in particular [5]. In patients suffering chronic pain, plastic changes with pain regulation in the central nervous system and peripheral nervous systems [6] [15][36] [42], psychological factors, and the like oftentimes retard medical treatment because they contribute to the formation of clinical conditions. However, it has been reported that the heart rate variability biofeedback method (HRV-BF method), in which fluctuations in a person's heart rate are increased by regulating respiration, lowers trait anxiety levels [32], and that it is effective against fibromyalgia syndrome, which is a model ailment when it comes to chronic pain [13].…”
Section: Availabilitymentioning
confidence: 99%
“…Dies war begleitet von einer Zunahme des rCBF (gemessen mit SPECT) im Thalamus und den Basalganglien und einer Abnahme des rCBF in einigen anderen Regionen, eine Korrelation mit klinischen Parametern fand sich nicht. Usui et al [70] untersuchten nichtdepressive Patienten mit FMS mit SPECT vor und nach einer Elektroschockbehandlung. Die Patienten gaben eine Besserung der Schmerzen an, und die Zahl der "tender points" war nach der Behandlung verringert.…”
Section: Verlaufsuntersuchungen Beim Fmsunclassified